Antonine women and the place names of the Roman Empire = Kobiety z kręgu Antoninów i nazwy miejscowe Cesarstwa Rzymskiego - Jurkowski, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article aims to highlight the increase in the number of place names derived from the names of the women associated with the Roman emperors that took place during the Antonines` era. In the first place the author will discuss astionyms, the etymology of which is unequivocally confirmed in the sources, followed by those, the provenance of which from matrons tied with the Antonines is less or more likely.
Keywords: nazwy miejscowe; kobiety; Cesarstwo Rzymskie; miasta; Antoninowie (dynastia; 96-192); place names; women; Antonine (dynasty; 96-192); cities; Roman Empire